2020
DOI: 10.1111/cts.12906
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Renal Preservation/Reperfusion Injury by Controlled Hyperthermia During Ex Vivo Machine Perfusion

Abstract: The possible reno-protective effect of a controlled brief heat-shock treatment during isolated ex vivo machine perfusion of donor grafts prior to reperfusion should be investigated in a primary in vitro study. Porcine kidneys (n = 14) were retrieved after 20 minutes of cardiac standstill of the donor and subjected to 20 hours of static cold storage in University of Wisconsin solution. Prior to reperfusion, kidneys were subjected to 2 hours of reconditioning machine perfusion with gradual increase in perfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The porcine kidney transplantation model has been widely used as a tool for clinical translational research . Renal perfusion is the basis for oxygen and nutrient transport, and quantitative assessment of transplanted kidney perfusion helps clinicians recognize the pathophysiological changes in the transplanted kidney . As shown in Figure A, to evaluate the effect of applying DSA trappers, an allogeneic porcine kidney transplantation model was successfully established, and the transplanted kidney perfusion was verified by multitemporal CT angiography.…”
Section: Resultsmentioning
confidence: 99%
“…The porcine kidney transplantation model has been widely used as a tool for clinical translational research . Renal perfusion is the basis for oxygen and nutrient transport, and quantitative assessment of transplanted kidney perfusion helps clinicians recognize the pathophysiological changes in the transplanted kidney . As shown in Figure A, to evaluate the effect of applying DSA trappers, an allogeneic porcine kidney transplantation model was successfully established, and the transplanted kidney perfusion was verified by multitemporal CT angiography.…”
Section: Resultsmentioning
confidence: 99%
“…Heat-shock proteins are well known as a defense mechanism induced by stressful stimuli such as hypoxia or hyperthemia ( 41 , 42 ). Minor et al demonstrated that with gradual rewarming (or “controlled hyperthermia”), they found a 50% increase of heat-shock proteins, which correlated to improvement of tubular reabsorption of sodium and glucose upon reperfusion, and reduced loss of urinary protein compared with controls, meriting further exploration of this technique in preclinical models ( 43 ). As a result of this work, there is emerging evidence that avoiding the abrupt temperature changes may be protective against IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Another group propagated a short period of hyperthermic perfusion (10 min at 42°C) of porcine kidneys (20 h SCS; 2 h perfusion with gradual increase of temperature to 35°C), as this led to a 50% increase of heat shock proteins, potentially inducing repair mechanism and tolerance against subsequent cellular injury [59].…”
Section: Optimization Of Normothermic Machine Perfusion Protocolsmentioning
confidence: 99%
“…As the Cytosorb adsorber is not cytokine specific and might even eliminate important anti-inflammatory mediators, the group further explored the use of a hemoadsorber to selectively remove pro-inflammatory cytokines. The use of a hemoadsorber resulted in a reduced expression of DGF-associated genes [58 Another group propagated a short period of hyperthermic perfusion (10 min at 428C) of porcine kidneys (20 h SCS; 2 h perfusion with gradual increase of temperature to 358C), as this led to a 50% increase of heat shock proteins, potentially inducing repair mechanism and tolerance against subsequent cellular injury [59].…”
Section: Optimization Of Normothermic Machine Perfusion Protocolsmentioning
confidence: 99%